2006
DOI: 10.1007/s10532-006-9097-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of ligninolytic enzymes and decolorization of molasses distillery wastewater by fungi under solid state fermentation

Abstract: Selected isolates of fungi were grown on wheat straw and corncob in the presence of different moistening agents such as water, molasses, potato dextrose broth and distillery effluent. All the fungal isolates responded differently with respect to growth and ligninolytic enzyme production. Fungal growth on different substrates was checked by calculating ergosterol content, which varied widely within a single species when grown on different substrates. The maximum laccase production was obtained for Aspergillus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 50 publications
4
39
0
2
Order By: Relevance
“…and Aspergillus fumigatus has been reported. 39 Pant and Adholeya 40 reported the production of LiP by Fusarium verticillioides and MnP by Aspergillus flavus, both fungi cultured in solid state fermentation. In the present study, extracellular LiP activity of R. oryzae ENHE was found in cultures with and without PCP, though this activity was higher when PCP was added to the culture medium.…”
mentioning
confidence: 99%
“…and Aspergillus fumigatus has been reported. 39 Pant and Adholeya 40 reported the production of LiP by Fusarium verticillioides and MnP by Aspergillus flavus, both fungi cultured in solid state fermentation. In the present study, extracellular LiP activity of R. oryzae ENHE was found in cultures with and without PCP, though this activity was higher when PCP was added to the culture medium.…”
mentioning
confidence: 99%
“…Most previous studies focused on the use of crude or pure laccases for the treatment of textile effluent (Wu et al 2002) or synthetic dyes (Li et al 2009). Pant et al studied solid state fermentation by fungi using distillery wastewater as a natural medium and achieved laccase production and decolorization (Pant et al 2007 However, reports on using dye-containing effluent as a natural medium for cultivation to obtain a decoloration effect have been rare. To the best of our knowledge, our study marked the first report on using a real textile effluent as the culture medium for simultaneous color removal and laccase production.…”
Section: Resultsmentioning
confidence: 99%
“…They found 75% decolourization with diluted wastewater which reduced to 40% on using undiluted wastewater. In another study, colour removal of 86, 50 and 47% was observed with Pleurotus florida, Penicillium pinophilum and Alternaria gaisen, respectively (Pant and Adholeya 2007b). Kaushik and Thakur (2009) isolated five different fungi from distillery mill site and the two isolates having higher capabilities to remove colour were identified as Emericella nidulans and Neurospora intermedia, respectively.…”
Section: Introductionmentioning
confidence: 96%